Reduced fibrin clot lysis in Klinefelter syndrome associated with hypogonadism - Simon Chang; Arkadiusz J Goszczak; Anne Skakkebæk; Jens Fedder; Anders Bojesen; M Vakur Bor; Moniek P M de Maat; Claus H Gravholt; Anna-Marie B Münster (Endocrine Connections, 2022)
Objective: Klinefelter syndrome (KS) is associated with increased risk of thrombosis. Hypogonadism and accumulating body fat in KS have a potential i mpact on fibrinolysis. In this study, we assessed the fibrinolytic system and the assoc iation with testosterone levels in KS. Design: This study is a cross-sectional comparison of men with KS and age-matched male controls. Methods: Fibrin clot lysis was evaluated by turbidity measurements and by measuring levels of individual fibrinolytic proteins in plasma samples. Fi brin clot structure was evaluated by scanning electron microscopy. Total testosterone was measured by liquid chromatography-tandem mass spectrometry. Body fat was evaluated by dual-energy X-ray absorptiometry. Results: In this study, 45 men with KS and 45 age- and education-matched controls were included. Men with KS had a 24% reduction in fibrin clot lysis c ompared with controls (46.2 ± 17.1 vs 60.6 ± 18.8 %/h, P = 0.0003) and higher levels of fibrinogen, factor XIII (P ≤ 0.01), and plasminogen activator inhibitor type 1 (P = 0.04). Men with KS had lower total testosterone (P = 0.008) and higher body fat (P = 0.001). In KS, reduced fibrin clot lysability was associated with higher fibrinogen and body f at related to decreasing total testosterone and hypogonadism among men with KS. Fibrin clot structure was not different compared to KS and controls. Conclusions: Fibrin clot lysis in KS was markedly reduced, potentially contributing to a prothrombotic state and increasing thrombotic risk. Hypogonadism in KS was associated with increased fibrinogen and total body fat, predicting reduced fibrin clot lysis.